Validity and Reliability of The Indonesian Modification of Score for Allergic Rhinitis - Asti Widuri; Rizka Fakhriani (Fakultas Kedokteran Universitas Lambung Mangkurat, 2021)
Abstract: Allergic rhinitis (AR) is a nasal inflammation caused by IgE-mediated reacions after inhaled the allergens. It’s characterized as symptoms of sneezing, airflow obstruction, nasal pruritus, and often clear nasal discharge. The prevalence of AR is about 5-40% in the general population and still rising. Multiple non-instrumental tests for AR were reported though few were validated. Score for Allergic Rhinitis (SFAR) is a valid instrument to screening AR. The purpose of this study was to perform adaptation and cultural translation and validation of the SFAR questionnaire for the Indonesian language. This was a cross sectional study to assess the validity and reliability of the Indonesian modification of Score for Allergic Rhinitis. The study conduct in 59 subjects. The Indonesian modification of SFAR instrument is valid and reliable as an instrument for screening AR with r values ranging from 0.345 to 0.730. Internal consistency shows that Cronbach's alpha is 0.803. The validation and reliability test of Indonesian modification of Score for Allergic Rhinitis was performed and valid and reliable as an instrument for assessing allergic rhinitis. Keywords: Allergic Rhinitis, Score for Allergic Rhinitis, Validity, Indonesian Version.